Skilled Immigration and the Employment Structures of US Firms - Kerr, Sari Pekkala; Kerr, William R.; Lincoln, William F. (Journal of Labor Economics, 2015)
We study the impact of skilled immigrants on the employment structures of US firms using matched employer-employee data. Unlike most previous work, we use the firm as the lens of analysis to account for greater heterogeneity and the fact that many skilled immigrant admissions are driven by firms themselves (e.g., the H-1B visa). OLS and IV specifications show rising overall employment of skilled workers with increased skilled immigrant employment by the firm. Employment expansion is greater for young natives than for their older counterparts. The departure rates for older workers relative to younger workers appear highest for those in STEM occupations.